Thalaba the Destroyer: Southey’s Nationalist “Romance” - Bolton, Carol (Romanticism on the Net, 2003)
AbstractThis article discusses the way in which Southey’s long narrative poem Thalaba the Destroyer (1801) reflected the process of his changing political position from radicalism to conservatism. My argument reveals that Southey’s use of oriental material in his poem complicated these political responses because his design was dominated by his imperialist ambitions for his own country. Southey’s representation of his young hero’s divine mission against magic, superstition and tyranny is therefore constructed in a way that discusses issues within British as well as Middle Eastern society. For instance, Southey’s depiction of Islam bifurcates into, on the one hand, a positive vision of ancient Islam—that is in fact a personal statement of his own beliefs and values—and on the other, a negative view of modern Islam as a “degraded” religion and society. It is Southey’s intention that the heroic role-model of personal morality and probity that he advocates in Thalaba (and which still operates as a device to criticize his own society, though it replaces his earlier political radicalism) be perceived as embodying ideal “British” characteristics. The supremacy of such “national” values in Southey’s text, justifies their dissemination into other cultures and societies abroad, so promoting here, as in his other works, Britain’s imperial policy abroad.